Family Quarrel: Joe Salsberg, the 'Jewish' Question, and Canadian Communism - Tulchinsky, Gerald (Labour/Le Travailleur, 2005)
Abstract Joseph Baruch Salsberg was one of Canada's best known and respected communists when he left the Labor-Progressive Party in 1957 after years of anguish over clear evidence of antisemitism in the Soviet Union. After a 30-year career in the Party in which he and numerous Jewish radicals had invested their belief that communism heralded a "better world's in birth" and solutions for all mankind's troubles, including the "Jewish question," Salsberg concluded that the poison of antisemitism was alive and well in the communist nirvana — and, with a broken heart, he walked away after vainly trying to convince Soviet leaders to reverse the trend.